The different positions of mandate of Al-waleed bin Yazid bin abd Al-malik (86-126 AH/705-744 AD) and the reaction of the Al-waleed towards those positions - الابراهيم يسرى صالح (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
The mandate of the Covenant is one of the important things that affected the Umayyad state, and was among the reasons that led to its fall. The passion of sonship controlled the successors of the sons of illiteracy, so they sought to change the crown prince even if he was the brother of the caliph, in order to appoint their children, as happened with the caliph Hisham bin Abd Al-Malik(105-125 AH/724-743 AD) who wanted to depose his crown Prince Al-Waleed bin Yazid bin abd Al-Malik to appoint one of his sons, and he tried to pressure al-Walid in various ways to do so, and this had a role in crystallizing the personality of al-Walid, who was described as poiytheist, The positions of Al-Walid differed according to the interests, as some supported it and others stood against it, the light that led to the third sedition and the emergence of conflict in the Umayyad family and the collapse of this state.